The Use of Audio-book to teach Pronunciation in Recount Text for 8th Graders of Junior High School (RETAIN, 2017)
The Use of Audio-book to teach Pronunciation in Recount Text for 8th Graders of Junior High School DzikrinaMardhotila English Education, Language and Art Faculty, State University Surabaya dotik059@gmail.com Fahri, M.A English Education Department, Faculty of Language and Art, State University of Surabaya fahri@unesa.ac.id Abstrak Hampir setiap permasalahan dalam pengucapan bahasa Inggristerjadi dipelajar bahasa Inggris. Menurut Hasan, 2004, mereka kebanyakan berfikir dalam bahasa induk mereka untuk pengucapan bahasa asing atau bahasa lain. Audio-book atu buku dalam bentuk audio ini dapat menjadi sebua hal ternatif untuk siswa belajar berbicara terutama cara pengucapan. Penelitian ini bertujuan untuk mendeskripsikan bagaimana Audio-book dapat berperansebagai media untuk belajar cara pengucapan yang benar di dalamteks recount dan pengaruh pada kemampuan pengucapan siswa di dalamteks recount dengan menggunakan Audio-book. Penelitia ini menggunakan prosedur kualitatif untuk mengumpulkan data dan menjawab semua pertanyaan yang ada. Penemuan menyebutkanbahwa guru mengadopsi 2 prosedur kegiatan penggunaan Audio-book yang tejadi didalam kelas, sedangkan kegiatan ketiga dilakukan olehsiswasendiri. Pengaruh dalam pengucapan siswa terlihat bahwa siswa mengalami peningkatan karna siswa dapat menyadari kesalahan pengucapan mereka dan merubahnya menjadi pengucapan yang benar. Kata Kunci : Audio-book, carapengucapan, teks recount Abstract Pronunciation problem have been in every Language learner. According to Hassan (2014) Second language will be hard for the learner because they think in L1, beside that mother tongue also affect their L2 on learning pronunciation. Audio-book is the one of to teach pronunciation in recount text. This study aims to describe how the Audio-book used to teach pronunciation in recount text and the effects’ of the students’ pronunciation in recount text by using Audio-book. Qualitative research was employed to collect the data and answer the research question. The findings show that the teacher adapted procedures and Audio-book was used twice in the classroom in different activity, the third activity conducted by the students itself. The effects’ of the student pronunciation show that Audio-book helps the students to aware of their mistakes and changes into proper pronunciation. Keyword: Audio-book, teaching pronunciation, recount text